Experimental studies on noise and vibration spectra of copy milling machines - Sergey V. Golosnoy; Alexander N. Chukarin (Advanced Engineering Research, 2016)
The research objective is to study the development of the noise spectra patterns in the operating area of copy mill operators. The experimental studies have shown that among harmful factors specific to these machines, there is an octave sound pressure level increase up to 15 dB in the idle mode and up to 15 dB under woodworking. These data suggest that the main noise source creating excess over the maximum permissible values is a spindle unit, and in particular, the spindle case. The vibration measurements on the machine carrier system have confirmed the results of the noise monitoring. The main source of the increased vibration levels for these machine tools is spindle rolling-contact bearings.